Isolation of denitrifying bacteria and cyanobacteria and their potential use in nitrate removal of well water in jaffna district - Thurairajah, A. (University of Jaffna, 2018)
Nitrate pollution of groundwater in the Jaffna Peninsula and its potential health hazards to the local population has been reported long past. This study aimed to identify bacterial and cyanobacterial strains suitable for bioremediation of nitrate contaminated water. Bacterial strains were isolated from various soil and water samples in the study area. Primary screening was carried out on Bromothymol blue (BTB) agar plate supplemented with KNO 3 . Assimilatory and dissimilatory nitrate reduction test was performed with Nessler’s reagent and nitrite reagent (sulfanilic acid and α-naphthylamine) respectively, in nutrient broth with KNO 3 . Quantitative screening was carried out in same nutrient broth with KNO 3 and NaNO 2 substrate separately. Suitability of carbon sources on bacterial nitrate removal was investigated using mineral salt medium containing either glucose or starch as the carbon sources and KNO 3 as the substrate. Carbon sources were optimized at three levels (0.25, 0.5 and 1.0 %) for efficient nitrate removal. Liberated gases during nitrate reduction were analyzed using Shimadzu GC-9 AM gas chromatography. Selected strains were identified by 165 rRNA homology analysis. Moreover, 28 cyanobacterial strains were also isolated using BG 11 medium and screened for nitrate reduction in synthetic medium. Ten well water samples having NO 3 -N concentration within the range of 15 mg/L to 57.37 mg/L were selected for treatment with selected strains. Treatment means were compared using Duncan’s multiple-range test at a significance level of 0.05. Out of 128 morphologically different bacterial stains 70 strains were identified as nitrate reducers. Among them, 38 strains were identified as dissimilatory nitrate reducers, out of which 21 strains showed more than 50% reduction of either nitrate or nitrite on nutrient broth with KNO 3 , and NaNO 2 , substrates respectively. Out of which, five strains showed greater nitrate reduction (above 70 %) either with glucose or starch. Among two carbon sources 0.5 % starch was found to be the best carbon source for efficient nitrate reduction with most of bacterial strains tested. The five strains were identified as Paracoccuspantotrophus, Paenibacillupolymyxa, Enterococcus casseliflavus, Klebsiella pneumonia and Pseudomonas aeruginosa. Two non-pathogenic strains namely, Paracoccuspantotrophus and Paenibacilluspolymyxa were used for water treatment. Five efficient nitrate reducing cyanobacterial strains were selected and tested with one water sample having 57.37 mg/L NO 3 -N. Cyanobacterial strains were identified as Limnothrixredekei (T8), Alkalinemapantanalense (T11), Filamentous cyanobacterium (T15), Limnothrixplanktonica (T20) and Geitlerinema sp. Both bacterial strains reduced NO 3 -N below safe level within 72 hours of treatment. Nitrate reduction percentage of strains Paracoccwpantotrophus and Paenibacilluspolymyxa were within the range of (59.63 — 100 %) and (86.67-100 %) respectively in different well water samples. However, co-culturing of these two strains was not successful in this study. Gas chromatography results indicated, the strains liberated higher percentage of N 2 , (68 - 90%) gas compared to other gases (N 2 O (5-13%) and trace of CO 2 ,) whilereducing nitrate. All tested cyanobacterial strains also reduced the nitrate below safe level at 14 th day ofculturing. Thus, the selected bacterial and cyanobacterial strains could be potentially used for removalof nitrate from water.
Keywords: Nitrate pollution; Denitrification; Bioremediation; Bacteria; Cyanobacteria